The OIB’s alleged scientific discourse against Sexual and Reproductive Policies - Gallas, Ana Kelma Cunha; Perez, Olívia Cristina (Argumentum, 2023)
This article addresses the discursive strategies adopted by the Observatório Interamericano de Biopolítica (OIB) to oppose Brazilian sexual and gender policies. It shows how the OIB uses supposedly scientific information, but without proof, to legitimise and disseminate its causes. We adopted a qualitative methodology, supported by documentary and bibliographic research. We analysed some of the OIB’s speeches at the 2014 “Gender, Abortion and Society” Seminar. The results show that the OIB uses typical troll science strategies to promote its arguments in environments considered secular, and also appeals to a “confirmation bias” strategy. The findings contribute to the understanding of discursive strategies used by anti-gender movements in contemporary times.